Continuing Medical Education and Continuing Professional Development in the Republic of Armenia: The Evolution of Legislative and Regulatory Frameworks Post Transition - Sharon Chekijian; Knarik Yedigaryan; Alexander Bazarchyan; Gevorg Yaghjyan; Sona Sargsyan (Journal of European CME, 2021)
The collapse of the Soviet Union in 1991 left many ex-republics in a financial and administrative crisis for the ensuing two decades. Previously centralised processes like recertification of doctors and healthcare workers and continuing medical education fell by the wayside. Continuing medical education and continuing professional development in Armenia have evolved through multiple phases from Soviet, to immediate, mid and late-transitional post-Soviet periods, to current modernising efforts. This manuscript describes the phases of evolution of continuing medical education chronologically and details the legislative and regulatory framework surrounding each stage of development. Armenia is currently implementing a credit system of continuing medical education with the aim to introduce and adopt new and efficient approaches in this field. Continuing education credits fall into three categories: didactic or theoretical knowledge, practical skills and self-education/self-development. To recertify, professionals must collect credits from all three groups with specified minimum amounts according to their degrees. Armenia’s guiding principle is to harmonise the continuing medical education and professional development model with internationally accepted criteria in order to contribute to the international mobility of healthcare workers and to provide for true on-going professional development and knowledge that will benefit our doctors, nurses and above all our patients.